BACTERIAL AND PATHOLOGICAL STUDIES ON CONDEMNED LIVERS OF ONE HUMPED CAMELS (Camelus dromedarius) SLAUGHTERED IN TAMBOOL SLAUGHTERHOSE, SUDAN - Mohammed, Nuseba H.; Osman, Halima M.; Y.A., Sabiel (Journal of Veterinary Medicine and Animal Production, 2021)
This study was carried out at Tambul slaughterhouse- Gezira State in the central Region of the Sudan to examine livers of camels slaughtered for human consumption, with special emphasis on the bacteriological and pathological changes. Ninety five liver specimens were collected randomly from slaughtered camels during the period (2010-2011) in duplicates. Each one of the duplicate specimens was placed in a sterile plastic container and studied bacteriologicaly by conventional bacteriological methods and rapid API strips were used for the identification of the isolates; and the other one was placed in 10% formalin for histpathological investigations. Among the gram positive isolated bacteria 25 (31.3%) were Staphylococcus spp., 10 (12.3%) Streptococcus.spp., 10 (12.3%) Micrococcus .spp.,5 (6.1%) Corynebacterium spp., 3 (3.7%) Bacillus cereus., 1(1.2%) Clostridium novyi., 1 (1.2%) Listeria monocytogenes and 1(1.2%) Lactobacillus plantarum .Gram-negative bacteria were 7 (8.6%) Pseudomonas aerogenosa, 6 (7.4%) Escherichia coli, 4 (4.9%) Acinetobacter and 3 (3.7%) Klebsiella pneumoniae, 4 (4.9%) yeast were recovered and one fungus (1.2%), Actinomyces viscosus. The results revealed that considerable numbers of pathogenic bacteria were observed with the end results of hepatic tissue degeneration and necrosis. Great attention should be taken in the slaughterhouse for appropriate evaluation of these pathogenic sources and only healthy livers should be passed for human consumption as generally it thecustom that camel livers are consumed uncooked (raw).